2022
DOI: 10.3389/fphar.2022.925276
|View full text |Cite
|
Sign up to set email alerts
|

Dapagliflozin Protects Methamphetamine-Induced Cardiomyopathy by Alleviating Mitochondrial Damage and Reducing Cardiac Function Decline in a Mouse Model

Abstract: Background: Methamphetamine (METH)-induced cardiovascular toxicity has been attributed to its destructive effect on mitochondrial function at least to some extent. Previous studies highlighted the benefits of dapagliflozin (DAPA) on the cardiovascular system, but the response of METH-induced cardiomyopathy to DAPA is never addressed before. The present study aimed to investigate the potential ability of DAPA in preventing METH-induced cardiomyopathy.Materials and Methods: C57BL/6 mice were randomly divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…DAPA showed a 1200-fold selectivity for SGLT2 over SGLT1 ( Zugner et al, 2022 ), and the effects of DAPA on mitochondrial complex I activity and amino acid metabolites have been reported ( Uthman et al, 2019 ; Mulder et al, 2020 ). Animal studies have suggested that DAPA may protect the myocardium from myocardial infarction ( Yu et al, 2021 ), obesity-related cardiomyopathy ( Lin K. et al, 2022 ), and methamphetamine-induced cardiomyopathy ( He S. et al, 2022 ). Cardiomyocytes and cardiac tissues lack SGLT2 expression, and the cardioprotective effects of SGLT2 inhibitors should be mediated by other targets and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…DAPA showed a 1200-fold selectivity for SGLT2 over SGLT1 ( Zugner et al, 2022 ), and the effects of DAPA on mitochondrial complex I activity and amino acid metabolites have been reported ( Uthman et al, 2019 ; Mulder et al, 2020 ). Animal studies have suggested that DAPA may protect the myocardium from myocardial infarction ( Yu et al, 2021 ), obesity-related cardiomyopathy ( Lin K. et al, 2022 ), and methamphetamine-induced cardiomyopathy ( He S. et al, 2022 ). Cardiomyocytes and cardiac tissues lack SGLT2 expression, and the cardioprotective effects of SGLT2 inhibitors should be mediated by other targets and signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“… 18 Some studies reported that DAPA attenuated cardiomyopathy by means of decreasing mitochondrial damage and apoptosis. 19 A previous study 9 showed that DAPA attenuated cardiac hypertrophy. Our study is consistent with it.…”
Section: Discussionmentioning
confidence: 99%